Análisis comparativo de los indicadores financieros en la gestión administrativa financiera de la “cooperativa de ahorro y crédito las Naves Ltda”, del cantón las Naves, provincia Bolívar, en el periodo 2016-2017 - Baños Villena, Dayana Gissela (2018)
The present research project, defined as a comparative analysis of the financial indicators, in the administrative and financial management of the Las Naves Ltda., Cooperative of Savings, Las Naves Canton, Bolívar province, whose main problem is how this analysis influences comparative in relation to the financial indicators developed by this institution, for this was taken as a sample to the periods 2016-2017, through this diagnosis has been detected that do not perform analysis in the financial statements, the main objective was to carry out a comparative analysis of financial indicators. To develop this research we used the inductive, deductive and historical method. The first one is in charge of analyzing the particular facts of the financial statements of the institution, the second compares the administrative management of each period and with the last method we get to know the results In addition, the instruments and techniques of data collection were applied, such as an interview addressed to the manager and presidents of councils, and a survey addressed to the officials and partners of the institution. For this study, a methodology was proposed to carry out a comparative analysis of the financial indicators for financial administrative management, through the application of proposed indicators to improve the financial performance of the cooperative